Which behavioral patterns score points in taekwondo matches? An analysis of the Roma 2019 World Grand Prix finalists - Quiñones Rodríguez, Yarisel; Apollaro, Gennaro; Fúnez, Carmen; Faelli, Emanuela; Hernández-Mendo, Antonio; Morales-Sánchez, Verónica; Falcó, Coral (Frontiers in Sports and Active Living, 2025)
IntroductionObservational methodology facilitates the study of situational factors in taekwondo matches, examines observable technical-tactical behaviors, and reveals various relationships, thus generating behavioral patterns. The aim of this study was to examine the technical-tactical scoring actions in the final matches of the Roma 2019 World Taekwondo Grand Prix, using polar coordinate analysis and function estimation.MethodsA point/nomothetic/multidimensional (P/N/M) observational design was applied, where the movements of all athletes were analyzed in relation to their behaviors and dimensions that align with the criteria of the observation instrument. Seven matches were observed (female, n = 3; male, n = 4) for a total of 1,382 registrations. The observation tool used for this study was designed “ad hoc” using the HOISAN tool. It consisted of five criteria (tactical action, technique type, strike area, sidedness, and scoring) and 30 categories. The tool was designed by three observers. Pearson's, Spearman's, and Kendall's tau-b interobserver and intraobserver correlation coefficients were estimated. Five focal categories related to the criterion “scoring” were considered: one point, two points, three points, four points, and five points. Relationships with a vector length ≥1.96 were considered significant (p < 0.05). A function estimation analysis was performed to validate the observed values (using linear, polynomial, exponential, and logarithmic regression, and polynomial interpolation) using Estimación de Funciones software.Results and discussionThe results allow for the development of new training and competition strategies based on the different technical-tactical actions that establish a significant pattern in the realization of a scoring action. Specifically, one point was obtained through a direct attack, a correction, or a subsequent counterattack. Two points were obtained through a simultaneous counterattack, while three points were obtained through an anticipation or a melee tactical action. Four points and five points were obtained through a direct attack or a simultaneous counterattack. Two points and three points were obtained with the left leg, while four points were obtained with the right leg. Moreover, three points and four points inhibited the right and left side of the body, respectively. Linear techniques were also inhibited when obtaining one point and five points, while circular techniques were used before or after one, two, and five points, showing that the circular technique was the most used.